Silver(II) oxide-mediated synthesis of 2, 4-diarylquinazolines. Issue 24 (13th June 2018) - Cheung, Wing; Patch, Raymond J.; Player, Mark R.
Graphical abstract: Highlights: One-pot synthesis of 2, 4-diarylquinazolines from N -arylbenzamides and benzylamines. Proceeds under neutral reaction conditions. Silver oxide-mediated 6π-electrocyclization/oxidation process. Broad scope with respect to N -arylbenzamides and benzylamine components. Abstract: A single-pot procedure for the synthesis of 2, 4-diarylquinazolines is described which involves a silver oxide-mediated CH activation/CN bond formation process. The generality of this method with respect to substituent effects is presented along with studies leading to process optimization. Mechanistic investigations provide support for the involvement of radical intermediates in the reaction process.